Efficient Non‐dissociative Activation of Dinitrogen to Ammonia over Lithium‐Promoted Ruthenium Nanoparticles at Low Pressure. (17th October 2019) - Zheng, Jianwei; Liao, Fenglin; Wu, Simson; Jones, Glenn; Chen, Tian‐Yi; Fellowes, Joshua; Sudmeier, Tim; McPherson, Ian J.; Wilkinson, Ian; Tsang, Shik Chi Edman
Abstract: There is an exciting possibility to decentralize ammonia synthesis for fertilizer production or energy storage without carbon emission from H2 obtained from renewables at small units operated at lower pressure. However, no suitable catalyst has yet been developed. Ru catalysts are known to be promoted by heavier alkali dopants. Instead of using heavy alkali metals, Li is herein shown to give the highest rate through surface polarisation despite its poorest electron donating ability. This exceptional promotion rate makes Ru–Li catalysts suitable for ammonia synthesis, which outclasses industrial Fe counterparts by at least 195 fold. Akin to enzyme catalysis, it is for the first time shown that Ru–Li catalysts hydrogenate end‐on adsorbed N2 stabilized by Li + on Ru terrace sites to ammonia in a stepwise manner, in contrast to typical N2 dissociation on stepped sites adopted by Ru–Cs counterparts, giving new insights in activating N2 by metallic catalysts. Abstract : Lithium‐Behandlung : Die Einführung von Li + in Ru‐basierte Katalysatoren kann adsorbierten Distickstoff auf der Metalloberfläche polarisieren und stabilisieren, was den nicht‐dissoziativen Weg zur Ammoniakbildung unter milden Bedingungen erleichtert. Die Li‐Ru‐Katalysatoren eignen sich für die umweltschonende Ammoniak‐Synthese bei niedrigerem Druck und sind deutlich besser als die kommerziellen Fe‐Katalysatoren.